Horizon scan of DNA-based methods for quality control and monitoring of herbal preparations - Raclariu-Manolică, Ancuța Cristina; Mauvisseau, Quentin; de Boer, Hugo J. (Frontiers in Pharmacology, 2023)
This article explores the latest advances in emerging DNA-based technologies and the opportunities they provide for evaluating the safety and quality of dietary supplements and herbal medicines. Herbal medicines and preparations are widely used in healthcare systems globally, but concerns remain about their quality and safety. New herbal products are constantly being introduced to the market under varying regulatory frameworks, with no global consensus on their definition or characterization. These biologically active mixtures are sold through complex globalized value chains, which create alarming concerns around contamination and profit-driven adulteration. Industry, academia, and regulatory bodies must collaborate to develop innovative strategies for the identification and authentication of botanicals and their preparations to ensure quality control. High-throughput sequencing (HTS) has significantly improved our understanding of the total species diversity within DNA mixtures. The standard concept of DNA barcoding has evolved over the last two decades to encompass genomic data more broadly. Recent research in DNA metabarcoding has focused on developing methods for quantifying herbal product ingredients to yield complementary results for regulatory questions. Novel techniques, such as loop-mediated isothermal amplification (LAMP), DNA barcode-based Recombinase Polymerase Amplification (BAR-RPA), DNA barcoding coupled with High-Resolution Melting (Bar-HRM), and microfluidics-based methods, offer more affordable tests for the detection of target species. While target capture sequencing and genome skimming considerably increasing the species identification resolution in challenging plant clades, ddPCR enables the absolute quantification of DNA in samples and could be used to detect intended and unwanted ingredients in herbal medicines.